Corpus Linguistics: Definition and areas of use - Alshehri, Ali Gharamah (Arab Journal for Sciences and Research Publishing, 2022)
Corpus linguistics is a modern linguistic field. It is believed to be a methodology that can be used in different kinds of linguistic research. The study aims at defining such methodology and indicating how it can supplement linguistic studies in various language research including phonology, morphology, lexicology, semantics, pragmatics, and discourse analysis. The current research explores corpus linguistics starting with stating its definition, and its most important tools such as collocations and concordance. Then, the study presents examples of ways in which corpus linguistics methodology can be used in linguistic research. The research also identifies the advantages and disadvantages of using such methodology to indicate when it should be used or avoided. The research concludes with the importance of corpus linguistics and indicates the various aspects of benefiting from it at different linguistic levels, whether this methodology is used alone or if it is used to support another methodology.